INFORMATIVE SUPPORT OF COURSE OF "PROJECTING OF EDUCATIONAL ENVIRONMENTS ON PHYSICS" (Journal of Information Technologies in Education (ITE), 2011)
The questions related to the necessity of informative support of course "Designing learning environments in physics. Emphasis is placed on the integrated nature of the discipline. The structure of the information environment of the course "Designing learning environments in physics".
Keywords: educational environment; future teachers of physics; informative support; pedagogical projecting